2014
DOI: 10.1371/journal.pone.0096283
|View full text |Cite|
|
Sign up to set email alerts
|

Opposing Effects of PI3K/Akt and Smad-Dependent Signaling Pathways in NAG-1-Induced Glioblastoma Cell Apoptosis

Abstract: Nonsteroidal anti-inflammatory drug (NSAID) activated gene-1 (NAG-1) is a divergent member of the transforming growth factor-beta (TGF-β) superfamily. NAG-1 plays remarkable multifunctional roles in controlling diverse physiological and pathological processes including cancer. Like other TGF-β family members, NAG-1 can play dual roles during cancer development and progression by negatively or positively modulating cancer cell behaviors. In glioblastoma brain tumors, NAG-1 appears to act as a tumor suppressor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…Furthermore, silencing TGFBR2 inhibited GDF15 activation of caspase 9 and caspase 3 in these cells. These results are in agreement with the results of other studies . Suppression of TGFBR2 by specific siRNA induced apoptosis via increasing cleavage of caspase 9 and 3 in A549 cells; this data is in agreement with previous findings and is in contradiction to other studies .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, silencing TGFBR2 inhibited GDF15 activation of caspase 9 and caspase 3 in these cells. These results are in agreement with the results of other studies . Suppression of TGFBR2 by specific siRNA induced apoptosis via increasing cleavage of caspase 9 and 3 in A549 cells; this data is in agreement with previous findings and is in contradiction to other studies .…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with the results of other studies. [32][33][34] Suppression of TGFBR2 by specific siRNA induced apoptosis via increasing cleavage of caspase 9 and 3 in A549 cells; this data is in agreement with previous findings 25,26 and is in contradiction to other studies. [35][36][37] Thus, the presence of TGFBR2 can mediate GDF15 inhibitory effect on cell proliferation.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, we analyzed how GDF-15 inhibits NF-κB in macrophages. Limited evidence exists that GDF-15 signals through the canonical TGF-β receptor and pathway (21)(22)(23). Phospho-SMAD2 and -3 (pSMAD2 and pSMAD3) mediate activation of canonical TGF-β signaling while the noncanonical pathway of TGF-β signals through the activation of phosphorylated TGF-β-activated kinase (pTAK1), leading to further downstream activation of NF-κB or the p38 MAP kinase (24,25).…”
Section: Gdf-15 Suppresses Macrophage Cytotoxic Activity By Inhibitinmentioning
confidence: 99%
“…Smad2, as the downstream effector of TGF-β1, can be activated by TGF-β1. Zhang and colleagues have reported that siRNAs to Smad2/Smad3 can partly abrogate the phosphoinositide 3-kinase (PI3k) inhibitor-promoted NAG-1-induced glioblastoma cell apoptosis [20]. Yang provided the first evidence that Smad2, but not Smad3, plays a critical role in TGF-β-induced apoptosis and gene expression [21].…”
Section: Introductionmentioning
confidence: 99%